A rapid degreasing method for light-curing slurry
By adopting a multi-stage thermal degreasing treatment process in photocured ceramic materials, the crack problem caused by gas escape during the heating process of ceramic materials is solved, and the high density and good mechanical properties of the ceramics are achieved.
Patent Information
- Application Number
- CN202310826861.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-19
- Filing Date
- 2023-07-07
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2043-07-07
AI Technical Summary
The existing photocured ceramic materials are prone to soften, break, and decompose into gases during heating, causing cracks in the product or sintering and densification to increase the difficulty, and the existing technology is difficult to take into account the ceramic performance requirements.
A rapid degreasing method of photocuring slurry is adopted. After printing the blank through a DLP photocuring printer, it is placed in a degreasing solvent and is subjected to thermal degreasing treatment. The thermal degreasing treatment process of ceramic blanks is strictly controlled, including multi-stage heating and Insulation is made to ensure that the entire thermal degreasing process is completed within 20 hours.
Effectively control the size of pores and the staged decomposition of polymers in resin system, find the balance between pore reduction and degreasing speed, so that photocured ceramics can achieve better performance in a short time, including high density, crack-free defects and good machinery performance.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a rapid degreasing method for photocurable slurry. Background Art
[0002] As one of the hot branches of additive manufacturing in recent years, photocuring additive manufacturing technology has the advantages of fast preparation speed and high precision. However, the content of photosensitive resin in it is relatively high, usually occupying more than 50% of the volume of the green body. It will soften, break, and decompose into gas and escape during the heating process, which has a direct impact on the performance of the resulting ceramic material and needs to be effectively controlled. Otherwise, it is easy to cause large defects in the product, such as cracks, or increase the difficulty of sintering and densification of the green body.
[0003] However, the current existing technologies mainly control the gas escape by adjusting the composition of the green body, such as regulating the resin content, or improving the material system, but the improvement effect is limited and it is difficult to take into account the performance requirements of the resulting photocured ceramics. Summary of the invention
[0004] The embodiment of the present invention provides a method for rapid degreasing of a photocurable slurry, aiming to solve the technical problems mentioned in the above background technology.
[0005] The embodiment of the present invention is implemented as follows: a method for rapid degreasing of a photocurable slurry, comprising:
[0006] The blank printed by the DLP light-curing printer using the light-curing slurry is immersed in a degreasing solvent, and then dried for standby use;
[0007] The dried green body is placed in a degreasing furnace for thermal degreasing treatment, with a heating rate of 0.1-0.5°C / min at 10-150°C and a heat preservation time of 70-80min; a heating rate of 0.5-1°C / min at 150-300°C and a heat preservation time of 55-65min; a heating rate of 1-1.5°C / min at 300-450°C and a heat preservation time of 40-50min; and a heating rate of 5-10°C / min at 450-1000°C and a heat preservation time of 20-30min.
[0008] The embodiment of the present invention strictly controls the thermal degreasing process of the ceramic body, slowly heats the body at 10°C, and gradually increases the heating rate in stages. The insulation time of each stage gradually decreases as the temperature rises, and the entire thermal degreasing process is controlled to be completed within 20 hours. The thermal degreasing process is conducive to manufacturing gas channels, controlling pore size, and reasonably controlling the staged decomposition of polymers in the resin system. It can effectively find a good balance between reducing pores and increasing the degreasing rate, and enables the light-cured ceramic to obtain better performance in a relatively short degreasing time. DETAILED DESCRIPTION
[0009] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0010] There needs to be enough gas channels for gas to escape, otherwise the gas that does not escape will cause a pressure difference inside and outside the green body, causing cracks in the green body. However, too many gas channels themselves will also become a part of the defect, bringing difficulties to the sintering and densification of the ceramic. The embodiment of the present application strictly controls the thermal degreasing process to manufacture gas channels, control the size of pores, and reasonably control the staged decomposition of polymers in the resin system, so as to find a better balance between reducing pores and increasing the degreasing speed, so that the light-cured ceramics can obtain better performance in a relatively short degreasing time.
[0011] Specifically, the embodiment of the present application provides a method for rapid degreasing of a photocurable slurry, comprising:
[0012] The blank printed by the DLP light-curing printer using the light-curing slurry is immersed in a degreasing solvent, and then dried for standby use;
[0013] The dried green body is placed in a degreasing furnace for thermal degreasing treatment, with a heating rate of 0.1-0.5°C / min at 10-150°C and a heat preservation time of 70-80min; a heating rate of 0.5-1°C / min at 150-300°C and a heat preservation time of 55-65min; a heating rate of 1-1.5°C / min at 300-450°C and a heat preservation time of 40-50min; and a heating rate of 5-10°C / min at 450-1000°C and a heat preservation time of 20-30min.
[0014] Preferably, the thermal degreasing treatment process is: heating rate of 0.3°C / min at 10-150°C, keeping warm for 75 minutes; heating rate of 0.8°C / min at 150-300°C, keeping warm for 60 minutes; heating rate of 1.3°C / min at 300-450°C, keeping warm for 45 minutes; and then heating rate of 8°C / min at 450-1000°C, keeping warm for 25 minutes.
[0015] In the embodiment of the present application, the relevant parameters of the DLP light-curing printer are set to brightness 25, grayscale 20, first layer exposure time 2s, single layer exposure time 15s, and the remaining parameters are automatically configured by the printer.
[0016] In the embodiment of the present application, the degreasing solvent may be one or more of dichloromethane, gasoline, kerosene, and n-heptane; preferably, the degreasing solvent is obtained by mixing dichloromethane and kerosene in a volume ratio of 5:95.
[0017] In the embodiment of the present application, the preparation method of the photocurable slurry is:
[0018] Weigh 10 to 30 parts of hydroxyethyl acrylate, 20 to 30 parts of hexanediol diacrylate, 10 to 20 parts of trimethylolpropane triacrylate, 10 to 40 parts of epoxy acrylate, 0.1 to 0.3 parts of photoinitiator, 1 to 5 parts of dispersant, 2 to 5 parts of paraffin wax and 0.1 to 0.5 parts of defoamer in parts by weight, place in a reaction device for mixing and stirring reaction, and obtain a photosensitive resin;
[0019] Weigh 20 to 30 parts of the photosensitive resin and 60 to 80 parts of ceramic powder by weight, place them in a ball mill for ball milling, and use a vacuum stirring device to perform defoaming treatment to obtain a photocurable slurry.
[0020] Wherein, the photoinitiator is one or more of trimethylbenzoyldiphenylphosphine oxide, trimethylbenzoylethylphosphonate, hydroxycyclohexylphenylketone, and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0021] Wherein, the dispersant is a polymer superdispersant; preferably, the dispersant is one or more of EFKA 4703, Solsperse AC7570, and Solsperse 41000.
[0022] The carbon number of hydrocarbons in the paraffin wax is 40 to 45 and the paraffin wax is solid at room temperature.
[0023] The ceramic powder is one or more oxide ceramic materials of zirconium oxide, aluminum oxide, and silicon oxide, and the average particle size is 0.1 to 2 μm. Although the embodiment of the present application only takes zirconium oxide as an example, those skilled in the art can understand that other oxide ceramic materials can also achieve the same effect.
[0024] Wherein, the defoaming agent is provided by Nanjing Jiazhong Chemical Technology Co., Ltd.
[0025] Examples of certain embodiments of the present application are given below, which are not intended to limit the scope of the present application.
[0026] In addition, it should be noted that the numerical values given in the following examples are as accurate as possible, but those skilled in the art understand that due to unavoidable measurement errors and experimental operation problems, each number should be understood as an approximate number rather than an absolutely accurate value.
[0027] Example 1
[0028] According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use;
[0029] Take 25 parts of the above photosensitive resin and 70 parts of zirconium oxide powder, mix them, and ball mill for 24 hours to obtain zirconium oxide photocurable slurry. Use DLP photocurable printer to prepare the blank. Prepare degreasing solvent with dichloromethane and kerosene in a volume ratio of 5:95, and heat it to 30°C in a water bath for use;
[0030] The printed photocured blank is washed and dried with distilled water, soaked in the above-mentioned degreasing solvent for 10 minutes, taken out and dried, and degreased in a degreasing furnace and heated to 1000°C. The heating rate is 0.2°C / min at 10-150°C and kept warm for 70 minutes; the heating rate is 0.6°C / min at 150-300°C and kept warm for 55 minutes; the heating rate is 1°C / min at 300-450°C and kept warm for 45 minutes; and then the heating rate is 7°C / min at 450-1000°C, kept warm for 25 minutes and then cooled in the furnace. After taking it out, sinter it at 1450°C for 2 hours to obtain the zirconium oxide sample. The density of the zirconium oxide sample obtained in this embodiment is 99.7%, without crack defects, the Vickers hardness is 16.8GPa, and the fracture toughness is 10.18MPa·m 1 / 2 , the bending strength is 653.2MPa.
[0031] Example 2
[0032] According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use;
[0033] Take 25 parts of the above photosensitive resin and 70 parts of zirconium oxide powder, mix them, and ball mill for 24 hours to obtain zirconium oxide photocurable slurry. Use DLP photocurable printer to prepare the blank. Prepare degreasing solvent with dichloromethane and kerosene in a volume ratio of 5:95, and heat it to 30°C in a water bath for use;
[0034] The printed photocured blank is washed and dried with distilled water, soaked in the above-mentioned degreasing solvent for 10 minutes, taken out and dried, and degreased in a degreasing furnace and heated to 1000°C. The heating rate is 0.3°C / min at 10-150°C and kept warm for 70 minutes; the heating rate is 0.5°C / min at 150-300°C and kept warm for 55 minutes; the heating rate is 1.2°C / min at 300-450°C and kept warm for 45 minutes; and then the heating rate is 9°C / min at 450-1000°C, kept warm for 20 minutes and then cooled in the furnace. After taking it out, sinter it at 1450°C for 2 hours to obtain the zirconium oxide sample. The density of the zirconium oxide sample obtained in this embodiment is 99.6%, without crack defects, the Vickers hardness is 16.2GPa, and the fracture toughness is 10.02MPa·m 1 / 2 , the bending strength is 650.9MPa.
[0035] Example 3
[0036] According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use;
[0037] Take 25 parts of the above photosensitive resin and 70 parts of zirconium oxide powder, mix them, and ball mill for 24 hours to obtain zirconium oxide photocurable slurry. Use DLP photocurable printer to prepare the blank. Prepare degreasing solvent with dichloromethane and kerosene in a volume ratio of 5:95, and heat it to 30°C in a water bath for use;
[0038] The printed photocured blank is washed with distilled water and dried, soaked in the above-mentioned degreasing solvent for 10 minutes, taken out and dried, and degreased in a degreasing furnace and heated to 1000°C. The heating rate is 0.5°C / min at 10-150°C and kept warm for 80 minutes; the heating rate is 1°C / min at 150-300°C and kept warm for 65 minutes; the heating rate is 1.5°C / min at 300-450°C and kept warm for 50 minutes; and then the heating rate is 10°C / min at 450-1000°C, kept warm for 30 minutes and then cooled in the furnace. After taking out, sinter at 1450°C for 2 hours to obtain the zirconium oxide sample. The density of the zirconium oxide sample obtained in this embodiment is 99.6%, without crack defects, the Vickers hardness is 15.9GPa, and the fracture toughness is 9.91MPa·m 1 / 2 , the bending strength is 645.7MPa.
[0039] Example 4
[0040] According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use;
[0041] Take 25 parts of the above photosensitive resin and 70 parts of zirconium oxide powder, mix them, and ball mill for 24 hours to obtain zirconium oxide photocurable slurry. Use DLP photocurable printer to prepare the blank. Prepare degreasing solvent with dichloromethane and kerosene in a volume ratio of 5:95, and heat it to 30°C in a water bath for use;
[0042] The printed photocured blank is washed and dried with distilled water, soaked in the above-mentioned degreasing solvent for 10 minutes, taken out and dried, and degreased in a degreasing furnace and heated to 1000°C. The heating rate at 10-150°C is 0.3°C / min, and the temperature is kept for 75 minutes; the heating rate at 150-300°C is 0.8°C / min, and the temperature is kept for 60 minutes; the heating rate at 300-450°C is 1.3°C / min, and the temperature is kept for 45 minutes; and then the heating rate at 450-1000°C is 8°C / min, and the temperature is kept for 25 minutes and then cooled in the furnace. After taking it out, sinter it at 1450°C for 2 hours to obtain the zirconium oxide sample. The density of the zirconium oxide sample obtained in this embodiment is 99.9%, without crack defects, the Vickers hardness is 17.3GPa, and the fracture toughness is 11.53MPa·m 1 / 2 , the bending strength is 668.4MPa.
[0043] Example 5
[0044] According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use;
[0045] Take 25 parts of the above photosensitive resin and 70 parts of zirconium oxide powder, mix them, and ball mill for 24 hours to obtain zirconium oxide photocurable slurry. Use DLP photocurable printer to prepare the blank. Prepare degreasing solvent with dichloromethane and kerosene in a volume ratio of 5:95, and heat it to 30°C in a water bath for use;
[0046] The printed photocured blank is washed and dried with distilled water, soaked in the above-mentioned degreasing solvent for 10 minutes, taken out and dried, and degreased in a degreasing furnace and heated to 1000°C. The heating rate is 0.4°C / min at 10-150°C, and kept warm for 75 minutes; the heating rate is 0.8°C / min at 150-300°C, and kept warm for 65 minutes; the heating rate is 1.5°C / min at 300-450°C, and kept warm for 45 minutes; and then the heating rate is 10°C / min at 450-1000°C, kept warm for 30 minutes, and then cooled in the furnace. After taking it out, sinter it at 1450°C for 2 hours to obtain the zirconium oxide sample. The density of the zirconium oxide sample obtained in this embodiment is 99.6%, without crack defects, the Vickers hardness is 16.1GPa, and the fracture toughness is 10.03MPa·m 1 / 2 , the bending strength is 647.9MPa.
[0047] Comparative Example 1
[0048] According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use;
[0049] Take 25 parts of the above photosensitive resin and 70 parts of zirconium oxide powder, mix them, and ball mill for 24 hours to obtain zirconium oxide photocurable slurry. Use DLP photocurable printer to prepare the blank. Prepare degreasing solvent with dichloromethane and kerosene in a volume ratio of 5:95, and heat it to 30°C in a water bath for use;
[0050] The printed photocured blank is washed with distilled water and dried, soaked in the above-mentioned degreasing solvent for 10 minutes, taken out and dried, and degreased in a degreasing furnace and heated to 1000°C. The heating rate at 10-150°C is 0.3°C / min, and the temperature is kept for 75 minutes; the heating rate at 150-300°C is 0.8°C / min, and the temperature is kept for 60 minutes; the heating rate at 300-450°C is 1.3°C / min, and the temperature is kept for 45 minutes; and then the heating rate at 450-1000°C is 2°C / min, and the temperature is kept for 25 minutes and then cooled in the furnace. After taking it out, sinter it at 1450°C for 2 hours to obtain the zirconium oxide sample. The density of the zirconium oxide sample obtained in this embodiment is 94.7%, with a small amount of crack defects, the Vickers hardness is 12.21GPa, and the fracture toughness is 7.88MPa·m 1 / 2 , the bending strength is 542.1MPa.
[0051] Comparative Example 2
[0052] According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use;
[0053] Take 25 parts of the above photosensitive resin and 70 parts of zirconium oxide powder, mix them, and ball mill for 24 hours to obtain zirconium oxide photocurable slurry. Use DLP photocurable printer to prepare the blank. Prepare degreasing solvent with dichloromethane and kerosene in a volume ratio of 5:95, and heat it to 30°C in a water bath for use;
[0054] The printed photocured blank is washed and dried with distilled water, soaked in the above-mentioned degreasing solvent for 10 minutes, taken out and dried, and degreased in a degreasing furnace and heated to 1000°C. The heating rate at 10-150°C is 0.3°C / min, and the temperature is kept for 75 minutes; the heating rate at 150-300°C is 0.8°C / min, and the temperature is kept for 90 minutes; the heating rate at 300-450°C is 1.3°C / min, and the temperature is kept for 105 minutes; and then the heating rate at 450-1000°C is 8°C / min, and the temperature is kept for 25 minutes and then cooled in the furnace. After taking it out, sinter it at 1450°C for 2 hours to obtain the zirconium oxide sample. The density of the zirconium oxide sample obtained in this embodiment is 93.1%, with a small amount of crack defects, a Vickers hardness of 11.44GPa, and a fracture toughness of 7.03MPa·m 1 / 2 , the bending strength is 530.5MPa.
[0055] Comparative Example 3
[0056] According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use;
[0057] Take 25 parts of the above photosensitive resin and 70 parts of zirconium oxide powder, mix them, and ball mill for 24 hours to obtain zirconium oxide photocurable slurry. Use DLP photocurable printer to prepare the blank. Prepare degreasing solvent with dichloromethane and kerosene in a volume ratio of 5:95, and heat it to 30°C in a water bath for use;
[0058] The printed photocured blank is washed with distilled water and dried, soaked in the above-mentioned degreasing solvent for 10 minutes, taken out and dried, and degreased in a degreasing furnace and heated to 1000°C. The heating rate is 1°C / min at 10-150°C and kept warm for 75 minutes; the heating rate is 1°C / min at 150-300°C and kept warm for 60 minutes; the heating rate is 1°C / min at 300-450°C and kept warm for 45 minutes; and then the heating rate is 5°C / min at 450-1000°C, kept warm for 25 minutes and then cooled in the furnace. After taking it out, sinter it at 1450°C for 2 hours to obtain the zirconium oxide sample. The density of the zirconium oxide sample obtained in this embodiment is 95.2%, with a small amount of crack defects, the Vickers hardness is 11.42GPa, and the fracture toughness is 8.03MPa·m 1 / 2 , the bending strength is 556.3MPa.
[0059] Comparative Example 4
[0060] According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use;
[0061] Take 25 parts of the above photosensitive resin and 70 parts of zirconium oxide powder, mix them, and ball mill for 24 hours to obtain zirconium oxide photocurable slurry. Use DLP photocurable printer to prepare the blank. Prepare degreasing solvent with dichloromethane and kerosene in a volume ratio of 5:95, and heat it to 30°C in a water bath for use;
[0062] The printed photocured blank is washed and dried with distilled water, soaked in the above-mentioned degreasing solvent for 10 minutes, taken out and dried, and degreased in a degreasing furnace and heated to 1000°C. The heating rate is 0.3°C / min at room temperature -150°C, and kept warm for 75 minutes; the heating rate is 0.8°C / min at 150-300°C, and kept warm for 60 minutes; the heating rate is 1.3°C / min at 300-450°C, and kept warm for 45 minutes; and then the heating rate is 8°C / min at 450-1000°C, kept warm for 25 minutes, and then cooled in the furnace. After taking out, sinter at 1450°C for 2 hours to obtain the zirconium oxide sample. The density of the zirconium oxide sample obtained in this embodiment is 97.8%, without crack defects, the Vickers hardness is 14.7GPa, and the fracture toughness is 8.28MPa·m 1 / 2 , the bending strength is 594.7MPa.
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A rapid degreasing method for a photocurable slurry, characterized in that: include: According to weight proportions, 20 parts of hydroxyethyl acrylate, 25 parts of hexanediol diacrylate, 15 parts of trimethylolpropane triacrylate, 25 parts of epoxy acrylate, 0.2 parts of trimethylbenzoyl diphenylphosphine oxide, 3 parts of EFKA4703, 4 parts of paraffin wax, and 0.3 parts of BYK1790 defoamer were mixed and stirred for 24 hours to obtain a photosensitive resin for later use; 25 parts of the above-mentioned photosensitive resin and 70 parts of zirconium oxide powder were mixed and ball-milled for 24 hours to obtain zirconium oxide photocurable slurry. A green body was prepared using a DLP photocurable printer. A degreasing solvent was prepared by mixing dichloromethane and kerosene in a volume ratio of 5:95, and heated to 30° C. in a water bath for later use. The printed photocured blank was washed and dried with distilled water, soaked in the above degreasing solvent for 10 minutes, taken out and dried, degreased in a degreasing furnace and heated to 1000°C, the heating rate at 10-150°C was 0.3°C / min, and kept warm for 75 minutes; the heating rate at 150-300°C was 0.8°C / min, and kept warm for 60 minutes; the heating rate at 300-450°C was 1.3°C / min, and kept warm for 45 minutes; then the heating rate at 450-1000°C was 8°C / min, kept warm for 25 minutes, then cooled in the furnace, taken out and sintered at 1450°C for 2 hours to obtain the zirconium oxide sample; The density of the obtained zirconia sample is 99.9%, there is no crack defect, the Vickers hardness is 17.3GPa, and the fracture toughness is 11.53MPa·m 1 / 2 , the bending strength is 668.4MPa.
Citation Information
Patent Citations
Ceramic slurry preparation and 3D (three dimensional) printing light curing molding method
CN106810215A
Photocuring ceramic slurry for 3D printing and pretreatment method of formed green body
CN113603467A